ENHANCEMENT OF ADDITIONAL CRIMINAL EFFECTIVENESS REVIEWS IN CORRUPTION CASES - Saritua Silitonga; Sarah Furqoni; Muhammad Dhobit Azhary Lubis; Surya Hamdani (Sean Institute, 2023)
It seems like you've provided a description of a specific corruption case and the challenges associated with prosecuting and recovering state losses in such cases. This paper discussed difficulties law enforcement faces when dealing with corruption cases and executing judgments related to the return of embezzled state funds. The case of I Putu Sudiartana, who was found guilty of corruption by a District Court Judge, exemplifies these challenges. The research methodology used in the case appears to be normative jurisdiction, which involves analyzing legal principles and regulations. The study draws on both primary data sources, obtained from informants and parties related to the issue, and secondary data sources, such as relevant documents and literature. The primary challenge highlighted is the difficulty in recovering state funds from corrupt individuals. Perpetrators of corruption often hide their ill-gotten gains in financial systems and legitimate business activities, making it challenging for law enforcement, including the Attorney General's office, to trace and seize these assets. The phrase